Physical properties of carbon nanotubes - Saito, R. (Imperial College Press, 1998)
This is an introductory textbook for graduate students and researchers from various fields of science who wish to learn about carbon nanotubes. The field is still at an early stage, and progress continues at a rapid rate. This book focuses on the basic principles behind the physical properties and gives the background necessary to understand the recent developments. Some useful computational source codes which generate coordinates for carbon nanotubes are also included in the appendix.
Keywords: Nanotubes.; Carbon.; Nanostructured materials.; elektronické knihy; electronic books